Portfolio constuction using robust weight functions - Mvubu, Thokozani (Division of Actuarial Science, 2014)
The Markowitz portfolio selection model has formed the foundation from which all the other portfolio selection models are formulated. The Sharpe Single Index and the Improved Sharpe Single Index models have been formulated in a bid to form better performing models. In the optimization algorithms, these models tend to not select highly volatile shares and thus eliminate the possibility of making better returns in the event these shares perform very well. The Huber and Tukey Bisquare weights are considered in this project to enhance these models in capturing these outlying observations. The Huber weights in the Improved Sharpe (Troskie-Hossain) Single Index model are found to be giving a better and more realistic optimal portfolio compared to the Sharpe Single Index model. 2